The mechanical and physical properties of thermoplastic natural rubber hybrid composites reinforced with hibiscus cannabinus, L and short glass fiber - Wan Busu, Wan Nazri; Anuar, Hazleen; Ahmad, Sahrim; Rasid, Rozaidi; Jamal, Nur Ayuni Jamal (Taylor & Francis, 2010)
Thermoplastic natural rubber hybrid composites reinforced with kenaf and short glass fibers were compounded by melt blending method using an internal mixer, Thermo Haake 600P. Thermoplastic natural rubbers (TPNR) were prepared from polypropylene (PP), natural rubber (NR) and liquid natural rubber (TPNR) with ratio 70:20:10, which were blended using internal mixer for 12 minutes at 180C and rotor speed 40 r.p.m. Glass fiber was treated with silane coupling agent while TPNR reinforced kenaf fiber composite is using MAPP as a compatibilizer. TPNR hybrid composite with kenaf/glass fibers was prepared with fiber content (5, 10, 15, 20 volume % of fiber). Mechanical properties of the composites were investigated using tensile test[1], flexural, impact, and hardness test and scanning electron microscope (SEM)[1]. The incorporation of the treated or untreated fiber into TPNR has result in an increment of almost 100% of flexural modulus and impact strength as compared to TPNR matrix. However, the maximum strain decreased with increasing fiber content. The optimum composition for hybrid composite is at the fiber ratio of 30% kenaf fiber and 70% glass fiber. The SEM micrograph had shown, that the composite with coupling agent or compatibilizer promote better fiber-matrix interaction.